Immediate weight bearing as tolerated versus delayed weight bearing following intramedullary fixation for geriatric intertrochanteric fractures: a post hoc analysis - Ning Li; Kai-Yuan Cheng; Jing Zhang; Gang Liu; Li Zhou; Shi-Wen Zhu; Ming-Hui Yang; Xin-Bao Wu; Xie-Yuan Jiang (BMC Musculoskeletal Disorders, 2024)
Abstract Background Early weight bearing is crucial for fracture healing after osteosynthesis for intertrochanteric fractures (ITFs). The optimal period to start weight bearing after surgery is still under debate. The aim of this study was to compare immediate weight bearing (IWB) as tolerated with delayed weight bearing (DWB) following intramedullary fixationin elderly ITF patients. Methods This post hoc analysis included patients aged ≥ 65 years with X-ray-confirmed ITFs who were admitted within 21 days after injury and who underwent intramedullary fixation surgery. The primary outcome was the EQ-5D score at 120 days after surgery. The secondary outcomes included the EQ-5D score at 30 days and 365 days after surgery, the complication rate and the mortality rate. Results Among 410 patients (190 IWB, 220 DWB), those in the IWB group had higher EQ-5D scores at 30 (P < 0.001) and 120 days (P = 0.002) but lower scores at 365 days (P = 0.012) than did those in the DWB group. There were no significant differences in the complication rates, reoperation rates, or one-year mortality rates between the groups. Conclusions Compared with delayed weight bearing, immediate weight bearing improves early functional outcomes without increasing the complication or mortality rates in elderly ITF patients.